The taxonomy and nomenclature of Kalanchoe humilis, K. prasina, and K. figueiredoi (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F. (Phytotaxa, 2020)
The taxonomy and nomenclature of Kalanchoe humilis, K. prasina, and K. figueiredoi (Crassulaceae subfam. Kalanchooideae) are discussed. Based on available evidence K. humilis and K. prasina are accepted as two species from eastern and south-tropical Africa, and K. figueiredoi is included in the synonymy of K. prasina.